(3GdGSJQGJjLjI (B-(3GdhXGFa (B-(3GdeLGdGJs - (3fLe YHhO(B, (3fLes ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2009)
(3eONd Gdi GdCYeGd GdGdcJQhfjI h GdEbJUGO GdGdcJQhfj h GdEOGQI GdEdcJQhfjI h ebhdI fgGjI GdGOGQI h GdhXGFa aj GdGOGQI GdGdcJQhfjI ef JNWjW h JfXje h bjGOI h QbGHI GVGaI Gdi GdCfJQfjJ h GdGSJQGJjLjI h GOGQI cd ef ehbY hGH h GdHQjO GdcJQhfj hGdHQeLjGJ hGdYed Yf HYO hGdJShjb GdGdcJQhfj h GdfbO GdGdcJQhfj hcPG GdTQcGJ GdGaJQGVjI h JWhQgG h GdeYQaI GdGdcJQhfjI h GdedcjI GdacQjI aj GdYUQ GdQbej(B.s
(3eQGLY (B:(3dcd aUd eQLYs
Keywords: (3GdGOGQIs; (3GdGOGQI GdGdcJQhfjIs; (3GdGYeGd GdGdcJQhfjIs; (3GdGfJQfJs